New territories of design between artisan heritage and historical sites of the city - Benedetto Inzerillo (Agathón)
The rediscovery of craftsmanship transcends the boundaries of the economy and invites us to reflect on what may be today creativity. Over the next decade, the most brilliant innovators, who have visions of new products with the potential to change the future, will no longer have to entrust to others the realization of their ideas but may produce and distribute themselves, taking advantage of the web and new technologies. The project Crezi_Food_Kit moves within this system. It involves the old town of Palermo starting from food and it tries to create a supply chain whose products, support each other in search of a new way where tradition and innovation walk side by side.